INOVASI SISTEM PENDIDIKAN - HM, Muhammad Anwar (Inspiratif Pendidikan, 2018)
Education is everything. Good civilization is one result of good education. When a community wants to achieve its goals well, education is the key to the answer. However, along with the changing times and times, education also changes in the patterns and methods of teaching. In addition, age, place, technological sophistication also forms learning patterns in education. Therefore, as time goes on as well as the demands of the times faced, it is very necessary for innovation in education itself. This is merely to meet the needs of the community as the main element in the education system. The writing below illustrates the importance of education in accordance with its stages and at the same time the demand for innovation.